2021
DOI: 10.1111/aogs.14263
|View full text |Cite
|
Sign up to set email alerts
|

The effects of obstetric emergency team training on patient outcome: A systematic review and meta‐analysis

Abstract: Introduction Little is known about the optimal simulation‐based team training in obstetric emergencies. We aimed to review how simulation‐based team training affects patient outcomes in obstetric emergencies. Material and methods Search Strategy: MEDLINE, Embase, Cochrane Library, and Cochrane Central Register of Controlled Trials were searched up to and including May 15, 2021. Selection criteria: randomized controlled trials (RCTs) and cohort studies on obstetric teams in high‐resource settings comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
(263 reference statements)
2
17
0
1
Order By: Relevance
“…The meta-analysis by Brogaard and colleagues, although finding evidence of potential positive effects of obstetric emergency simulation-based team training on risk of neonatal brachial plexus injury (but with a low-certainty level of evidence) and Apgar scores <7, (though this finding failed to achieve statistical significance), found no evidence of a beneficial effect on other outcomes including hypoxic-ischemic encephalopathy. 1 Their findings are similar to other reviews in this area, including a 2020 Cochrane review that concluded multi-professional emergency obstetric training may have positive effects on practical skills, knowledge, and team behavior, but there is little high-certainty evidence of a positive effect on patient outcome. 2 Only 4 of the 21 studies included in Brogaard's metaanalysis were randomized controlled trials, the remainder were retrospective cohort studies.…”
Section: Commentsupporting
confidence: 70%
“…The meta-analysis by Brogaard and colleagues, although finding evidence of potential positive effects of obstetric emergency simulation-based team training on risk of neonatal brachial plexus injury (but with a low-certainty level of evidence) and Apgar scores <7, (though this finding failed to achieve statistical significance), found no evidence of a beneficial effect on other outcomes including hypoxic-ischemic encephalopathy. 1 Their findings are similar to other reviews in this area, including a 2020 Cochrane review that concluded multi-professional emergency obstetric training may have positive effects on practical skills, knowledge, and team behavior, but there is little high-certainty evidence of a positive effect on patient outcome. 2 Only 4 of the 21 studies included in Brogaard's metaanalysis were randomized controlled trials, the remainder were retrospective cohort studies.…”
Section: Commentsupporting
confidence: 70%
“… 16 31 34 A recent systematic review and meta-analysis has found weak evidence to support an effect on brachial plexus injury; and a positive but non-significant effect on Apgar scores below 7 at 5 min; the evidence supporting other clinical outcomes was less clear. 35 Indeed, emergency obstetric training programme evaluations routinely demonstrate changes in the first three levels of the Kirkpatrick Evaluation Model: a systematic literature review assessed the evidence for the effectiveness of training in emergency obstetric care, and included 101 studies. 10 Changes in level 1 and/or level 2 were investigated in 68 of these, with level 3 assessed in 51 studies, and level 4 in 21.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the low response rate at 6 months and 12 months post-MANE, along with the characteristics of survey respondents may have affected responses provided at these time points, and the lack of clinical outcome data further limits the interpretation of this study. It is worth noting, however, that the evidence supporting clinical outcomes following obstetric training programmes is unclear, 35 or the length of time they are sustained. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Efforts to standardise ISS terms and concepts and develop an integrated model of learning is required [ 2 , 4 , 17 ]. Previous reviews have focused on ISS for education and training of healthcare professionals [ 18 ], ISS in operating rooms [ 19 ], effect on patient outcomes [ 20 ] or have included ISS within a broader simulation approach within acute care settings [ 21 ], for caesarean section training [ 22 ] and obstetric emergency teams [ 23 ]. Reviews have highlighted a limited but promising evidence base for ISS and reported high variability of ISS approaches to design, delivery, and evaluation [ 18 23 ].…”
Section: Introductionmentioning
confidence: 99%